Zebrafish Patient-Derived Xenograft Model as a Preclinical Platform for Uveal Melanoma Drug Discovery - Jie Yin; Gangyin Zhao; Helen Kalirai; Sarah E. Coupland; Aart G. Jochemsen; Gabriel Forn-Cuní; Annemijn P. A. Wierenga; Martine J. Jager; B. Ewa Snaar-Jagalska; Arwin Groenewoud (MDPI AG, 2023)
Uveal melanoma (UM) is a rare malignant cancer of the eye, with up to 50% of patients dying from metastasis, for which no effective treatment is available. Due to the rarity of the disease, there is a great need to harness the limited material available from primary tumors and metastases for advanced research and preclinical drug screening. We established a platform to isolate, preserve, and transiently recover viable tissues, followed by the generation of spheroid cultures derived from primary UM. All assessed tumor-derived samples formed spheroids in culture within 24 h and stained positive for melanocyte-specific markers, indicating the retention of their melanocytic origin. These short-lived spheroids were only maintained for the duration of the experiment (7 days) or re-established from frozen tumor tissue acquired from the same patient. Intravenous injection of fluorescently labeled UM cells derived from these spheroids into zebrafish yielded a reproducible metastatic phenotype and recapitulated molecular features of the disseminating UM. This approach allowed for the experimental replications required for reliable drug screening (at least 2 individual biological experiments, with n > 20). Drug treatments with navitoclax and everolimus validated the zebrafish patient-derived model as a versatile preclinical tool for screening anti-UM drugs and as a preclinical platform to predict personalized drug responses.